Recontextualization of Translanguaging in the Context of Mandarin Language Teaching in Indonesia - Nan, Guan; Angelina, Lia; Silalahi, Ronald Maraden Parlindungan; Santoso, Wulandari (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Translanguaging is interpreted as one of the pedagogical strategies for learning foreign languages in a multilingual context where there is the use of several languages for receptive and productive purposes. The purpose of this study was to explore the perceptions of teachers of Mandarin as a Second Language regarding translanguaging (cross-language) approaches in classroom learning. This research method is qualitative research with a foreign language applied linguistic approach. The research data comes from the Focused Discussion Group as the main data source and the Google Form questionnaire as a supporting data source. The FGD was conducted with 12 lecturers at a private university that has a Chinese Language study program. The data obtained were analyzed descriptively according to the results of the FGD. The results of the FGD stated that most of the teachers gave a positive response to translanguaging and that there was the implementation of translanguaging in the classroom by the teachers in a flexible way with a variety of language choices. Translanguaging often occurs when dealing with students with low linguistic abilities where the lecturer uses a language other than the target language when explaining vocabulary, terms and proverbs as well as when giving examples, this reflects the main purpose of implementing translanguaging for most informants is to increase and deepen understanding students on the material. Through this research process, it can be concluded that in the Mandarin pedagogical context, teachers tend to provide tolerance and flexibility for the existence of translanguaging.